Pengaruh Beauty Influencer dan Perceived Price Fairness Terhadap Keputusan Pembelian Produk Skincare - Sherli; Lilik Noor Yuliati; Nur Hasanah (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Due to the rapid increase of beauty influencer and global skincare product numbers, local skincare brands need to consider the most appropriate beauty influencer and pricing in order to attract potential consumers. This study aims to analyze the effect of beauty influencers and perceived price fairness on purchasing decisions through brand personality, brand trust and brand image. This research was conducted through an online survey using a voluntary sampling technique to 200 respondents with the criteria; consumers of skin care products aged 20-35 years who have made purchases in the last three months, have social media accounts and have seen beauty influencer reviews. Data were analyzed using Structural Equation Modeling (SEM) Lisrel. The results showed that the effect of beauty influencer and perceived price fairness had an indirect influence on purchasing decisions through intervention variables. Beauty influencers have a significant influence on purchasing decisions through brand personality, brand trust and brand image. Meanwhile, the perceived price fairness has a significant influence on purchasing decisions through brand image.